2016
DOI: 10.5194/acp-16-7957-2016
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of upper stratospheric wintertime tracer variability into the Arctic spring and summer

Abstract: Abstract. Using data from the Aeronomy of Ice in the Mesosphere (AIM) and Aura satellites, we have categorized the interannual variability of winter-and springtime upper stratospheric methane (CH 4 ). We further show the effects of this variability on the chemistry of the upper stratosphere throughout the following summer. Years with strong wintertime mesospheric descent followed by dynamically quiet springs, such as 2009, lead to the lowest summertime CH 4 . Years with relatively weak wintertime descent, but … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…2 are consistent with similar calculations in Smith et al (2011) and Straub et al (2012), for the general shape of the trajectory and in that the parcels do not originate above approximately 100 km. The parcels at 80 • N arrive from higher altitudes due to a stronger vertical component of the circulation compared to 67 • N. Conversely, the horizontal component of the circulation is stronger at 67 • N and the parcels arriving there originate from lower latitudes compared to those arriving at 80 • N. The magnitude of the TEM wind is larger for the higher altitudes, as is also shown in Smith et al (2011), and the air parcels that arrive above 66 km altitude originate in the summer hemisphere. The parcels that arrive below this altitude, which could be considered as part of the Brewer-Dobson circulation (Brewer, 1949), originate at latitudes closer to the equator.…”
Section: Trajectories During Arctic Wintersupporting
confidence: 58%
See 3 more Smart Citations
“…2 are consistent with similar calculations in Smith et al (2011) and Straub et al (2012), for the general shape of the trajectory and in that the parcels do not originate above approximately 100 km. The parcels at 80 • N arrive from higher altitudes due to a stronger vertical component of the circulation compared to 67 • N. Conversely, the horizontal component of the circulation is stronger at 67 • N and the parcels arriving there originate from lower latitudes compared to those arriving at 80 • N. The magnitude of the TEM wind is larger for the higher altitudes, as is also shown in Smith et al (2011), and the air parcels that arrive above 66 km altitude originate in the summer hemisphere. The parcels that arrive below this altitude, which could be considered as part of the Brewer-Dobson circulation (Brewer, 1949), originate at latitudes closer to the equator.…”
Section: Trajectories During Arctic Wintersupporting
confidence: 58%
“…The TEM zonal-mean tracer continuity equation has been described in various works (e.g. Garcia and Solomon, 1983;Andrews et al, 1987;Brasseur and Solomon, 2005;Monier and Weare, 2005;Smith et al, 2011):…”
Section: The Tem Continuity Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…Randall et al (2009) suggest that, in these cases, VMRs of EPPproduced NO x are controlled more by mesosphere and lower thermosphere (MLT) descent rates than by the structure of the vortex. Siskind et al (2016) found that due to downward transport of methane (CH 4 ) in years with strong, uninterrupted mesospheric descent, summertime upper stratospheric chlorine monoxide (ClO) is about 50 % greater than in years with strong horizontal transport.…”
Section: Introductionmentioning
confidence: 99%